Anti-static film and preparation method thereof

By using a combination of modified acrylic resin and acetylene glycol additives in the antistatic film, combined with the process of online coating and synchronous lateral stretching, the problems of apparent textures and bubble points of the antistatic film during the coating process are solved. , realizes high-quality antistatic film preparation.

CN119463257APending Publication Date: 2025-02-18HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411709572.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the antistatic film has defects such as apparent traces and bubble points during the high-speed coating process, which affects the overall quality of the film.

Method used

The anti-static layer of modified acrylic resin and acetylene glycol additive is used to form a three-dimensional network structure to improve anti-static performance and apparent quality through online coating.

Benefits of technology

Excellent apparent quality and anti-static properties are achieved, and the surface resistance is in the range of 104Ω-1011Ω, which significantly improves the overall performance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463257A_ABST
    Figure CN119463257A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of anti-static, and provides an anti-static film and a preparation method thereof, the anti-static film comprises a support body and an anti-static layer, and at least one surface, in contact with air, of the support body is coated with the anti-static layer. The anti-static layer contains a conductive material, modified acrylic resin, a cross-linking agent, an alkynediol auxiliary agent and deionized water, so that the anti-static layer can be coated on a base material to uniformly form a film. Therefore, by utilizing the synergistic effect of the water-based conductive material, the modified acrylic resin and the modification additive under the online coating process, the surface resistance of the anti-static layer of the prepared anti-static film can reach 10 < 4 >-10 < 11 > omega, and the anti-static film has excellent and stable anti-static property and high apparent quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antistatic, and in particular relates to an antistatic film and a preparation method thereof. Background Art

[0002] Optical films in liquid crystal displays are increasingly used. During transportation and deep processing, these optical films will be contaminated by static electricity, resulting in various drawbacks during deep processing and affecting the overall quality of the optical films. Therefore, it is necessary to cover the surface of the optical film with an antistatic protective film.

[0003] In addition, although the protective film is the material to be peeled off in the end, if there are defects such as bubbles and coating lines on the surface of the protective film, it is not certain whether the defect is caused by the polarizer or the protective film. Therefore, in the field of high-end antistatic films, it is required to have both excellent antistatic performance and high surface performance.

[0004] At present, antistatic films can be divided into two types: internal addition type and coating type. Among them, there are two coating processes for coating antistatic films, one is offline coating and the other is online coating. Since the online coating antistatic film has a high resistance value and its application range is limited, the offline coating antistatic film is widely used. Online coating antistatic film is to apply the antistatic coating liquid to the surface of the film during the film manufacturing process, but on the one hand, the coating thickness is limited and the coating thickness is low, generally tens of nanometers; on the other hand, it needs to be stretched 3 to 5 times after coating, resulting in the weakening of the antistatic performance or the disappearance of the antistatic performance, so the coating performance requirements are very high. Therefore, the antistatic film used in the release film and protective film industry is mostly antistatic film prepared by offline process.

[0005] However, in the high-speed coating process of the antistatic film in the prior art, there are problems such as surface texture and bubble points of the antistatic film. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides an antistatic film and a preparation method thereof. The antistatic layer of the present invention uses a modified acrylic resin in combination with an acetylene glycol auxiliary agent, and has a high-quality coating appearance.

[0007] The present invention includes the following technical solutions: an antistatic film, comprising a substrate and an antistatic layer disposed on at least one side of the substrate, wherein the antistatic layer and the substrate are synchronously stretched transversely and then shaped to obtain the antistatic film; the antistatic layer is composed of the following weight parts of a conductive material, a modified acrylic resin, a crosslinking agent, an acetylene glycol auxiliary agent, and deionized water;

[0008] Conductive material: 5 to 10 parts by weight;

[0009] Modified acrylic resin: 5-10 parts by weight;

[0010] Cross-linking agent: 0.1 parts by weight to 5 parts by weight;

[0011] Deionized water: 74 parts by weight to 89.9 parts by weight;

[0012] Alkyne diol auxiliary agent: 0.01 parts by weight to 1 parts by weight.

[0013] As an improved technical solution of the present application, the structure of the acetylene glycol auxiliary agent is:

[0014]

[0015] Wherein, the R1 is selected from C1-C8 straight-chain alkanes; and the R2 is selected from C1-C8 straight-chain alkanes.

[0016] As an improved technical solution of the present application, the conductive material is one or more of a polythiophene-like dispersion, a carbon nanotube dispersion, and a polyaniline dispersion.

[0017] As an improved technical solution of the present application, the modified acrylic resin is a fluorine-containing acrylic resin.

[0018] As an improved technical solution of the present application, the modified acrylic resin is copolymerized by soft monomer, hard monomer and functional monomer; the weight ratio of soft monomer to hard monomer is 1:1 to 1:0.8; the weight ratio of soft monomer to functional monomer is 1:1 to 1:0.5;

[0019] The soft monomer is a combination of one or more of ethyl acrylate, butyl acrylate or octyl acrylate in any weight ratio;

[0020] The hard monomer is a combination of one or more of methyl methacrylate or styrene in any weight ratio;

[0021] The functional monomer is a combination of one or more of hexafluorobutyl methacrylate or 1H,1H-perfluorooctyl acrylate in any weight ratio.

[0022] As an improved technical solution of the present application, the initiator used for the modified acrylic resin is ammonium persulfate or potassium persulfate, or a combination of the two in any weight ratio.

[0023] As an improved technical solution of the present application, the emulsifier used for the modified acrylic resin is a combination of one or more of sodium acrylamide stearate or sodium 2-acrylamide-2,2-dimethylethanesulfonate in any weight ratio.

[0024] As an improved technical solution of the present application, the alkaline neutralizer used for the modified acrylic resin is one of hexamethylenediamine, n-butylamine, dimethylethanolamine or ammonia water.

[0025] As an improved technical solution of the present application, the cross-linking agent is one of oxazolines, isocyanates, nitrogen pyridines, and melamines.

[0026] Another object of the present application is to provide a method for preparing an antistatic film, which is used for the antistatic film, and the method comprises the following steps:

[0027] Feeding the substrate raw material into the extrusion system to melt and extrude the substrate melt;

[0028] forming the substrate melt into an amorphous cast slab on a cooling roll;

[0029] Preheating the cooled cast thick sheet and then longitudinally stretching it 3.0 to 5.0 times to obtain a membrane sheet;

[0030] Coating an antistatic coating liquid on one surface of the film;

[0031] The film coated with the antistatic coating liquid is preheated and then stretched transversely by 3.0 to 5.0 times to obtain a film;

[0032] The film is heat-set to obtain an antistatic film.

[0033] By adopting the above technical solution, the present invention has the following advantages:

[0034] 1. The antistatic coating liquid of the present invention uses an acetylene glycol auxiliary agent, and the coating liquid has good dynamic spreading performance. The acetylene glycol structure in the present invention forms a hydrophobic-hydrophilic-hydrophobic structure, and the highly branched structure is helpful for the dispersion of the antistatic coating liquid, and further improves the antistatic performance of the coating and the coating appearance.

[0035] 2. The method of the present invention comprises the following steps: the antistatic coating liquid is prepared by combining modified acrylic resin, water-based conductive material, crosslinking agent and modified acetylene glycol auxiliary agent, and the antistatic coating liquid is applied online, and the antistatic coating liquid is stretched and fixedly heat-cured synchronously with the substrate in the transverse direction to form a three-dimensional network structure; the surface resistance is 10 4 Ω-10 11 Ω antistatic film has excellent surface quality and antistatic performance.

[0036] 3. The modified acrylic resin of the present invention is safe and environmentally friendly, has good film-forming properties, and excellent physical and mechanical properties. It can form an interpenetrating network with an antistatic agent through online coating and stretching, and the coating with the interpenetrating network polymer has better optical properties. In order to improve the dynamic spreading performance and antistatic performance of the water-based antistatic coating liquid, a modified acetylene glycol additive is used. The water-based modified acrylic resin is used as an interpenetrating network polymer, which has the characteristics of good dynamic wetting effect and the like.

[0037] 4. The present invention improves the cross-linking effect through molecular structure design, so that the coating has excellent antistatic performance. At the same time, the modified acrylic resin and the water-based conductive polymer material are stretched and shaped synchronously with the substrate through online coating, and thermally cured to form a three-dimensional network structure, forming a dense conductive path. The surface resistance of the obtained antistatic film is 10 4 Ω~10 11 Ω, with excellent anti-static performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 This is a schematic diagram of the structure of an antistatic film in an embodiment of the present invention;

[0040] In the accompanying drawings: 1-substrate, 2-antistatic layer.

[0041] Figure 2 Comparative Example 1: Antistatic layer coating apparent defects diagram.

[0042] Figure 3 This is a diagram showing the apparent defects of the antistatic coating of 2 in an antistatic film comparative example.

[0043] Figure 4 This is a diagram showing the apparent defects of the antistatic coating of 3 in an antistatic film comparative example.

[0044] Figure 5 This is a diagram showing the apparent defects of the antistatic coating of 4 in an antistatic film comparative example.

[0045] Figure 6 This is an apparent diagram of the antistatic coating of Examples 1-5 of the antistatic film. DETAILED DESCRIPTION

[0046] like Figure 1As shown, an antistatic film comprises a substrate 1 and an antistatic layer 2 provided on at least one side of the substrate 1, wherein the antistatic layer and the substrate 1 are synchronously stretched transversely and then shaped to obtain the antistatic film, wherein the antistatic layer comprises the following parts by weight of a conductive material, a modified acrylic resin, a crosslinking agent, an acetylene glycol auxiliary agent, and deionized water;

[0047] Conductive material: 5 to 10 parts by weight;

[0048] Modified acrylic resin: 5-10 parts by weight;

[0049] Cross-linking agent: 0.1 parts by weight to 5 parts by weight;

[0050] Deionized water: 74 parts by weight to 89.9 parts by weight;

[0051] Alkyne diol auxiliary agent: 0.01 parts by weight to 1 parts by weight.

[0052] Among them, if the content of the conductive material is too low, the antistatic effect is poor; if the content of the conductive material is too high, the spreading performance of the coating liquid is reduced, the coating appearance is poor, and the transparency of the film will also be affected, so the preferred weight percentage of the conductive material is 5 to 10 parts by weight.

[0053] If the content of modified acrylic resin is too low, the film-forming effect of conductive material on the film surface is poor, the coating appearance is poor, and the transparency of the film will also be affected; if the content of modified acrylic resin is too high, the conductive material is wrapped too tightly, and there is too little conductive material exposed on the surface, and the antistatic performance is difficult to exert, resulting in poor antistatic effect. Therefore, the preferred weight percentage of modified acrylic resin is 5 to 10 parts by weight.

[0054] If the cross-linking agent content is too low, the cross-linking density of the coating will be too low, and the hardness and scratch resistance of the antistatic coating will be reduced. If the cross-linking agent content is too high, the stability of the coating liquid will be poor. At the same time, too many small molecules will lead to excessive cross-linking, and high temperature will easily cause risks such as precipitation. Therefore, the weight percentage of the cross-linking agent is preferably 0.1 to 5 parts by weight.

[0055] The acetylene glycol structure set in the present application is based on the performance of acetylene glycol in reducing dynamic surface tension. At the same time, acetylene glycol forms a hydrophobic-hydrophilic-hydrophobic structure and a highly branched structure, which helps to disperse the carbon nanotube coating liquid and improve the antistatic performance and coating appearance.

[0056] In some embodiments, the acetylene glycol auxiliary agent has a structure of:

[0057]

[0058] Wherein, the R1 is selected from C1-C8 straight chain alkanes; the R2 is selected from C1-C8 straight chain alkanes. Since the acetylene glycol surfactant has multiple functions such as wetting, defoaming, improving the dispersibility of the system, improving the flow and leveling properties; it has excellent dynamic wettability, can quickly and effectively reduce the surface tension of the system, and has low foaming. A satisfactory defoaming effect can be obtained by adding a small amount, and the acetylene glycol has a good effect on controlling microbubbles. The present invention forms a hydrophobic-hydrophilic-hydrophobic structure by controlling the ratio of hydrophobic and hydrophilic groups in the acetylene glycol, which is highly branched.

[0059] In some embodiments, the conductive material is one or more of a polythiophene dispersion, a carbon nanotube dispersion, and a polyaniline dispersion. The purpose is to improve the antistatic performance of the coating and prevent the electrostatically adsorbed dust generated during the preparation of the protective film from causing poor product quality.

[0060] In order to improve the crosslinking density of the antistatic coating, ensure that the linear molecules are connected to each other to form a three-dimensional network structure, improve the weather resistance of the antistatic coating and form a dense conductive path, while ensuring the stability of the antistatic liquid. In some embodiments, the crosslinking agent is one of oxazolines, isocyanates, nitrogen pyridines, and melamines.

[0061] Another object of the present application is to provide a method for preparing an antistatic film, which is used to prepare the antistatic film, and the method comprises the following steps:

[0062] Feeding the substrate raw material into the extrusion system to melt and extrude the substrate melt;

[0063] forming the substrate melt into an amorphous cast slab on a cooling roll;

[0064] Preheating the cooled cast thick sheet and then longitudinally stretching it 3.0 to 5.0 times to obtain a membrane sheet;

[0065] Coating an antistatic coating liquid on one surface of the film;

[0066] The film coated with the antistatic coating liquid is preheated and then stretched transversely by 3.0 to 5.0 times to obtain a film; the longitudinal stretching by 3.0 to 5.0 times can ensure the uniformity of the longitudinal thickness and ensure that the longitudinal stretching is not too large and the orientation degree is too high, which makes it difficult to form a film during transverse stretching;

[0067] The film is heat-set to obtain an antistatic film.

[0068] In some embodiments, the modified acrylic resin is a fluorine-containing acrylic resin.

[0069] In other embodiments, the method for preparing the modified acrylic resin of this embodiment comprises the following steps:

[0070] Mix 46.8-69.3% deionized water and 0.1-0.6% emulsifier evenly and add them to the reactor; raise the temperature from room temperature to 125-135°C, add 30-50% mixed monomers and 0.1-0.6% initiator to the reactor in a dropwise manner, and continue the dropwise addition for 2-4 hours; keep warm for 1-2 hours after the dropwise addition is completed to terminate the reaction; after the reaction is completed, cool to 80-90°C and add 0.5-2% alkali neutralizer, add deionized water after full neutralization, and stir to emulsify the product for 1-2 hours; continue stirring for 1-1.5 hours, then cool to room temperature to obtain modified acrylic resin. % in this link refers to weight percentage.

[0071] The mixed monomer is composed of a soft monomer, a hard monomer and a functional monomer, the weight ratio of the soft monomer to the hard monomer is 1:1 to 1:0.8; the weight ratio of the soft monomer to the functional monomer is 1:1 to 1:0.5; the soft monomer is one or any combination of ethyl acrylate, butyl acrylate or octyl acrylate; the hard monomer is one or any combination of methyl methacrylate or styrene; the functional monomer is one or any combination of hexafluorobutyl methacrylate or 1H,1H-perfluorooctyl acrylate. By selecting a mixed monomer of soft monomers, hard monomers and functional monomers for copolymerization, the coating has the functions of flexibility, hardness and adhesion.

[0072] The initiator used in the modified acrylic resin is one of ammonium persulfate and potassium persulfate or a combination thereof, so as to provide free radicals and initiate polymerization reaction during the preparation of the modified acrylic resin.

[0073] The emulsifier used for the modified acrylic resin is one of sodium acrylamide stearate or sodium 2-acrylamide-2,2-dimethylethanesulfonate or a combination thereof, so as to achieve uniform dispersion and form a stable modified acrylic resin emulsion.

[0074] The alkaline neutralizer used in the modified acrylic resin is one of hexamethylenediamine, n-butylamine, dimethylethanolamine or ammonia water, in order to adjust the pH value of the modified acrylic resin and ensure the stability of the water-based acrylic resin.

[0075] Specifically, when used, the type and content of each component can be arbitrarily selected within the above range, and the prepared modified acrylic resin does not have a significant effect on the performance of the antistatic layer coating liquid.

[0076] Example 1

[0077] Preparation of antistatic coating liquid:

[0078] Take 5g of water-based polyaniline dispersion HS0394 (Foshan Nanhai Jiangshun Chemicals, the weight ratio of polyaniline in the water-based polyaniline dispersion is 5%), 5g of modified acrylate resin, 89.9g of deionized water, 0.1g of oxazoline crosslinking agent WS-700 (Youen Chemicals), and 0.01g of acetylene glycol auxiliary agent (BASF). Use a high shear emulsifier to disperse them evenly to prepare an antistatic layer coating liquid.

[0079] Preparation of antistatic film:

[0080] First, the crystallized and dried polyester chips are fed into the corresponding extrusion system for melt extrusion, and then cast on a rotating cooling roll. The cooled cast sheet is preheated and longitudinally stretched, and the longitudinal stretching ratio is 3 times. The prepared antistatic layer coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic layer coating liquid is heated and dried, and then stretched transversely by 3 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 70nm. Figure 5 shown.

[0081] Example 2

[0082] Preparation of the antistatic layer coating solution:

[0083] Take 7.5g of water-based polythiophene dispersion A200 (Agfa, the weight ratio of polythiophene in the water-based polythiophene dispersion is 5%), 7.5g of modified acrylic resin, 82.5g of deionized water, 2.5g of melamine crosslinking agent LF-8500 (Funeng Resin), and 1g of acetylene glycol auxiliary agent (BASF). Use a high shear emulsifier to disperse them evenly to prepare an antistatic coating liquid.

[0084] Preparation of antistatic film:

[0085] First, the crystallized and dried polyester chips are sent to the corresponding extrusion system for melt extrusion and cast on a rotating cooling roller. The cooled cast sheet is preheated and longitudinally stretched with a longitudinal stretching ratio of 4 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried and then transversely stretched 4 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 105nm.

[0086] Example 3

[0087] Preparation of the antistatic layer coating solution:

[0088] Take 10g of aqueous carbon nanotube dispersion ML1293 (Jingkang Biotechnology, the weight ratio of carbon nanotubes in the aqueous carbon nanotube dispersion is 5%), 10g of modified acrylic resin, 75g of water, 5g of oxazoline crosslinking agent WS-700 (Youen Chemical), and 0.5g of acetylene glycol auxiliary agent (BASF). Use a high shear emulsifier to disperse them evenly to prepare an antistatic coating liquid.

[0089] Preparation of antistatic film:

[0090] First, the crystallized and dried polyester chips are sent to the corresponding extrusion system for melt extrusion and cast on a rotating cooling roller. The cooled cast sheet is preheated and longitudinally stretched with a longitudinal stretching ratio of 5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried, and then transversely stretched 5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 140nm.

[0091] Example 4

[0092] Preparation of the antistatic layer coating solution:

[0093] Take 8.75g of water-based polythiophene dispersion A200 (Agfa, the weight ratio of polythiophene in the water-based polythiophene dispersion is 5%), 8.75g of modified acrylic resin, 79.25g of water, 3.25g of nitrogen pyridine crosslinking agent SAC-100 (Youn Chemical), and 0.25g of acetylene glycol auxiliary agent (BASF). Use a high shear emulsifier to disperse them uniformly to prepare an antistatic coating liquid.

[0094] Preparation of antistatic film:

[0095] First, the crystallized and dried polyester chips are sent to the corresponding extrusion system for melt extrusion and cast on a rotating cooling roller. The cooled cast sheet is preheated and longitudinally stretched with a longitudinal stretching ratio of 4.5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried and then transversely stretched 4.5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 120nm.

[0096] Example 5

[0097] Preparation of the antistatic layer coating solution:

[0098] Take 6.25g of water-based polyaniline dispersion HS0394 (Foshan Nanhai Jiangshun Chemicals, the weight ratio of polyaniline in the water-based polyaniline dispersion is 5%), 6.25g of modified acrylic resin, 86.25g of water, 1.25g of oxazoline crosslinking agent WS-700 (Youen Chemicals), and 0.75g of acetylene glycol auxiliary agent (BASF). Use a high shear emulsifier to disperse them uniformly to prepare an antistatic coating liquid.

[0099] Preparation of antistatic film:

[0100] First, the crystallized and dried polyester chips are sent to the corresponding extrusion system for melt extrusion and cast on a rotating cooling roller. The cooled cast sheet is preheated and longitudinally stretched with a longitudinal stretching ratio of 3.5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods such as gravure coating, wire rod coating, and dip coating. The film coated with the antistatic coating liquid is heated and dried, and then transversely stretched 3.5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 85nm.

[0101] Comparative Example 1

[0102] Preparation of antistatic coating liquid:

[0103] Take 6.25g of water-based polyaniline dispersion HS0394 (Foshan Nanhai Jiangshun Chemicals, the weight ratio of polyaniline in the water-based polyaniline dispersion is 5%), 6.25g of unmodified acrylic resin, 86.25g of water, 1.25g of oxazoline crosslinking agent WS-700 (Youen Chemicals), and 0.75g of polyether siloxane auxiliary agent (Di Gao). Use a high shear emulsifier to disperse them evenly to prepare an antistatic coating liquid.

[0104] Preparation of antistatic film:

[0105] First, the crystallized and dried polyester chips are fed into the corresponding extrusion system for melt extrusion and cast on a rotating cooling roll. The cooled cast sheet is preheated and longitudinally stretched, and the longitudinal stretching ratio is 3.5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried, and then stretched transversely by 3.5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 85nm. Figure 2 shown.

[0106] Comparative Example 2

[0107] Preparation of antistatic coating liquid:

[0108] Take 8.75g of aqueous polythiophene dispersion A200 (Agfa, the weight ratio of polythiophene in the aqueous polythiophene dispersion is 5%), 8.75g of modified acrylic resin, 79.25g of water, and 3.25g of oxazoline crosslinking agent WS-700 (Youen Chemical), and disperse them evenly with a high shear emulsifier to prepare an antistatic coating liquid.

[0109] Preparation of antistatic film:

[0110] First, the crystallized and dried polyester chips are fed into the corresponding extrusion system for melt extrusion and cast on a rotating cooling roll. The cooled cast sheet is preheated and longitudinally stretched, and the longitudinal stretching ratio is 4.5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried, and then stretched transversely by 4.5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 120nm. Figure 3 shown.

[0111] Comparative Example 3

[0112] Preparation of antistatic coating liquid:

[0113] Take 10g of water-based polyaniline dispersion HS0394 (Foshan Nanhai Jiangshun Chemicals, the weight ratio of polyaniline in the water-based polyaniline dispersion is 5%), 10g of unmodified acrylic resin, 75g of water, 5g of oxazoline crosslinking agent WS-700 (Youen Chemicals), and 0.75g of common acetylene glycol auxiliary agent (Fufei Chemicals). Use a high shear emulsifier to disperse them evenly to prepare an antistatic coating liquid.

[0114] Preparation of antistatic film:

[0115] First, the crystallized and dried polyester chips are fed into the corresponding extrusion system for melt extrusion and cast on a rotating cooling roll. The cooled cast sheet is preheated and longitudinally stretched with a longitudinal stretching ratio of 5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried and then transversely stretched 5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 140nm. Figure 4 shown.

[0116] Comparative Example 4

[0117] Take 8.75g of water-based polythiophene dispersion A200 (Agfa, the weight ratio of polythiophene in the water-based polythiophene dispersion is 5%), 8.75g of unmodified acrylic resin, 79.25g of water, 3.25g of nitrogen pyridine crosslinking agent SAC-100 (Youn Chemical), and 0.25g of acetylene glycol auxiliary agent (BASF). Use a high shear emulsifier to disperse them uniformly to prepare an antistatic coating liquid.

[0118] Preparation of antistatic film:

[0119] First, the crystallized and dried polyester chips are fed into the corresponding extrusion system for melt extrusion and cast on a rotating cooling roll. The cooled cast sheet is preheated and longitudinally stretched, and the longitudinal stretching ratio is 4.5 times. The prepared antistatic coating liquid is coated on one side or both sides of the longitudinally stretched film by one of the methods of gravure coating, wire rod coating, dip coating, etc. The film coated with the antistatic coating liquid is heated and dried, and then stretched transversely by 4.5 times, and then heat-set and rolled up to obtain an antistatic film with a coating dry thickness of 120nm. Figure 5 shown.

[0120] The performance test methods are as follows:

[0121] (1) Surface resistance (antistatic layer): measured according to GB / T 33398;

[0122] (2) Coating appearance quality: visual inspection under strong flashlight. The coating appearance is divided into three categories: ○ for those without defects such as blooming, vertical lines or bubbles, △ for those with slight blooming, vertical lines or bubbles, and × for those with severe blooming, vertical lines or bubbles.

[0123] (3) Dynamic spreading performance: tested using a SITA t15 dynamic surface tension meter.

[0124] The test results are shown in Table 1:

[0125] Table 1 Test results of embodiments and comparative examples

[0126] Test items Surface resistance(Ω) Coating surface quality Transmittance T(%) Dynamic surface tension (mN / m) Example 1 <![CDATA[10 8 Oh]]> ○ 89.7 36.2 Example 2 <![CDATA[10 7 Oh]]> ○ 89.8 34.3 Example 3 <![CDATA[10 4 Oh]]> ○ 90.3 35.4 Example 4 <![CDATA[10 5 Oh]]> ○ 89.7 35.8 Example 5 <![CDATA[10 7 Oh]]> ○ 89.0 34.8 Comparative Example 1 <![CDATA[>10 12 Oh]]> × 88.9 42.1 Comparative Example 2 <![CDATA[10 6 Oh]]> △ 89.2 44.0 Comparative Example 3 <![CDATA[>10 12 Oh]]> × 88.8 39.0 Comparative Example 4 <![CDATA[>10 12 Oh]]> × 89.3 38.3

[0127] It can be seen from the comparison between Comparative Example 1 and Example 5 that after using modified acrylic resin and acetylene glycol additives in Example 5, the surface resistance of the coating after online coating and biaxial stretching is 10 7 Ω, the coating appearance is good. Figure 2 As shown, the coating in Comparative Example 1 has flowery and longitudinal white lines on the surface.

[0128] It can be seen from the comparison between Comparative Example 2 and Example 4 that the antistatic layer of Comparative Example 2 does not contain modified acetylene glycol additives, and the surface resistance is 106 Ω, the antistatic performance is not as good as that of adding modified acetylenic diol additives, and the coating appearance is also poor. Figure 3 As shown, the coating in Comparative Example 2 has flowery and longitudinal white lines on the surface.

[0129] It can be seen from the comparison between Comparative Example 3 and Example 5 that after using modified acrylic resin and acetylene glycol as additive in Example 5, the surface resistance of the coating after online coating and biaxial stretching is 10 7 Ω, the coating surface is good. While the surface resistance of comparative example 3 is >10 12 Ω, no anti-static properties, like Figure 4 As shown, the coating in Comparative Example 3 has obvious flowery and longitudinal whitening defects.

[0130] It can be seen from the comparison between Comparative Example 4 and Example 4 that Example 4 uses modified acrylic resin with modified acetylene glycol additives. Compared with ordinary acrylic resin with modified acetylene glycol additives, the surface resistance of the coating after online coating and biaxial stretching is 10 7 Ω, the coating surface is good. While the surface resistance of comparative example 4 is >10 12 Ω, no anti-static performance, poor appearance, and low light transmittance. Figure 5 As shown, the coating in Comparative Example 4 has the defects of flowery and longitudinal white lines.

[0131] It can be seen from the comparison between Example 1 and Example 5 that the modified acrylic resin and polyaniline in the coating of Example 5 are more than those in Example 1, the more effective antistatic components per unit area, and the better antistatic effect achieved.

[0132] It can be seen from Table 1 that the antistatic film prepared in the embodiment of the present invention is significantly improved in terms of the antistatic performance of the antistatic layer and the coating appearance compared with the antistatic film prepared in the comparative example, indicating that the antistatic polyester film of the present invention not only has excellent antistatic performance, but also has excellent coating liquid stability, good continuous processing performance, and good application prospects.

[0133] Please combine Figure 2-Figure 5 Supplementary Examples and Comparative Examples

[0134] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. An antistatic film, comprising a substrate (1) and an antistatic layer (2) disposed on at least one side of the substrate (1), wherein the antistatic layer and the substrate (1) are synchronously stretched transversely and then shaped to obtain the antistatic film; characterized in that: The antistatic layer (2) is composed of the following parts by weight of a conductive material, a modified acrylic resin, a crosslinking agent, an acetylene glycol auxiliary agent and deionized water; Conductive material: 5 to 10 parts by weight; Modified acrylic resin: 5-10 parts by weight; Cross-linking agent: 0.1 parts by weight to 5 parts by weight; Deionized water: 74 parts by weight to 89.9 parts by weight; Alkyne diol auxiliary agent: 0.01 parts by weight to 1 parts by weight.

2. An antistatic film as claimed in claim 1, characterized in that: The structure of the acetylene glycol auxiliary agent is: Wherein, the R1 is selected from C1-C8 straight-chain alkanes; and the R2 is selected from C1-C8 straight-chain alkanes.

3. An antistatic film as claimed in claim 1, characterized in that: The conductive material is one or more of a polythiophene dispersion, a carbon nanotube dispersion, and a polyaniline dispersion.

4. An antistatic film as claimed in claim 1, characterized in that: The modified acrylic resin is a fluorine-containing acrylic resin.

5. An antistatic film as claimed in claim 1 or 4, characterized in that: The modified acrylic resin is copolymerized by soft monomers, hard monomers and functional monomers; The weight ratio of the soft monomer to the hard monomer is 1:1 to 1:0.8; the weight ratio of the soft monomer to the functional monomer is 1:1 to 1:0.5; The soft monomer is a combination of one or more of ethyl acrylate, butyl acrylate or octyl acrylate in any weight ratio; The hard monomer is a combination of one or more of methyl methacrylate or styrene in any weight ratio; The functional monomer is a combination of one or more of hexafluorobutyl methacrylate or 1H,1H-perfluorooctyl acrylate in any weight ratio.

6. An antistatic film as claimed in claim 5, characterized in that: The initiator used for the modified acrylic resin is ammonium persulfate or potassium persulfate, or a combination of the two in any weight ratio.

7. An antistatic film as claimed in claim 5, characterized in that: The emulsifier used for the modified acrylic resin is a combination of one or more of sodium acrylamide stearate or sodium 2-acrylamide-2,2-dimethylethanesulfonate in any weight ratio.

8. An antistatic film as claimed in claim 5, characterized in that: The alkaline neutralizing agent used for the modified acrylic resin is one of hexamethylenediamine, n-butylamine, dimethylethanolamine or ammonia water.

9. An antistatic film as claimed in claim 1, characterized in that: The cross-linking agent is one of oxazolines, isocyanates, nitrogen pyridines and melamines.

10. A method for preparing an antistatic film, characterized in that: For preparing the antistatic film according to any one of claims 1 to 9, the method comprises the following steps: Feeding the substrate raw material into the extrusion system to melt and extrude the substrate melt; forming the substrate melt into an amorphous cast slab on a cooling roll; Preheating the cooled cast thick sheet and then longitudinally stretching it 3.0 to 5.0 times to obtain a membrane sheet; Coating an antistatic coating liquid on one surface of the film; The film coated with the antistatic coating liquid is preheated and then stretched transversely by 3.0 to 5.0 times to obtain a film; The film is heat-set to obtain an antistatic film.